The Rate of Conversion from Immune-tolerant Phase to Early Immune-clearance Phase in Children with Chronic Hepatitis B Virus Infection - Hong, Suk Jin (The Korean Society of Pediatric Gastroenterology, Hepatology and Nutrition, 2014)
PURPOSE: The spontaneous seroconversion rate of hepatitis B e antigen (HBeAg)-positive chronic hepatitis B (CHB) virus infection in children is lower than that in adults. However, few studies have investigated the rate of transition from the immune-tolerant to the early immune-clearance phase in children. METHODS: From February 2000 to August 2011, we enrolled 133 children aged <18 years who had visited the Department of Pediatrics, Kyungpook National University Hospital. All subjects were in the immune-tolerant phase of HBeAg-positive CHB virus infection. The estimated transition rate into the early immune-clearance phase was calculated using the Kaplan-Meier method. RESULTS: Among the 133 enrolled pediatric CHB virus infection patients in the HBeAg-positive immune-tolerant phase, only 21 children (15.8%) had converted to the early immune-clearance phase. The average age at entry into active hepatitis was 10.6±4.8 years. The incidence of transition from the immune-tolerant to the early immune-clearance phase in these children was 1.7 episodes/100 patient-years. When analyzed by age, the estimated transition rate was 4.6%, 7.1%, and 28.0% for patients aged <6, 6-12, >12 years, respectively. CONCLUSION: In children with CHB virus infection, the estimated rate of entry into the early immune-clearance phase was 28.0% for patients aged 12-18 years, which was significantly higher than that observed for children aged <12 years (11.7%; p=0.001).